Design Of An Effective Hybrid Cryptographic Technique For Information Security In Cloud Computing - Anjana; Singh, Dr.Ajit (Migration Letters, 2024)
The cloud computing technology of the future offers high availability, virtualization, and dynamic resource pools. Cloud computing is a technique to tackle typical computing problems, such as hardware, software, and resource availability, without the involvement of computer users. The two most significant issues with cloud computing are cloud security and cloud implementation over the network. There are lot of cryptographic algorithms existing to encrypt the data in cloud storage but with various loopholes. The proposed solution is a hybrid technique utilizing RSA, Blowfish, and MD5; it enables users to exchange data securely within a cloud environment. MD5 is currently the most prevalent symmetric cryptography algorithm. It is crucial to build a high-performance variant of MD5 to expand its wider application. The RSA as well as Blowfish encryption method is used to encrypt data when a cloud user uploads it to the cloud environment. The cloud controller can use his or her own private key to decrypt the data. Cloud computing is a tried-and-true, scalable, and effective approach for offering services. Finally, performance evaluation has been completed by contrasting the outcomes of the proposed hybrid technique with those of the existing techniques.